Girişimcilik ve girişimcilerin kişilik özellikleri konusunda bir uygulama - Demircan, Nigar (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2000)
In this dissertation, the terms of entrepreneur and entrepreneurship are '" and the importance of supporting entrepreneurship and developing entrepreneurial personality traits is mentioned. Important personality traits of entrepreneurs and demographic, social and psychologic factors which influence entrepreneurship are told in detail. Using 97 small company owners in Düzce, in this study, the relationship of the entrepreneurs' need for achievement, power and affiliation to their entrepreneurial personality traits is examined. The differences between these traits, based on the demographic, social and psychologic factors, are also investigated. As a result of this study, some interesting findings have been obtained. It is determined that, the factors which mostly effect the small business owners in Düzce, to found their own company, are the desires to earn more money and be their own boss. Most of the entrepreneurs reflect the entrepreneurial personality traits which are commonly mentioned in literature. One of the important results of this study indicate that entrepreneurial personality traits are related to need for achievement and power. According to the findings, concerning their personality traits, the entrepreneurs who had spent most of their lives in urban areas are different from the others.
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: İşletme; Business Administration